The Use of 5-Alpha Reductase Inhibitors Improves the Detection of Prostate Cancer by Increasing Opportunities for Repeated Prostate-Specific Antigen Testing: A Decade-Long (2007–2016) Nationwide Observational Study in Korea - Young Hwii Ko; Sang Won Kim; Hoseob Kim; Yoon-Jong Bae (Journal of Urologic Oncology, 2023)
Purpose The aim of this study was to investigate the influence of taking 5-alpha reductase inhibitors (5ARIs) on the detection of prostate cancer (PCa), considering the reported low uptake of prostate-specific antigen (PSA) testing among Korean men. Materials and Methods From Korean National Health Insurance Sharing Service data, the number of men older than 40 years who were prescribed 5ARIs from 2007 through 2016 was identified. The association of 5ARI prescriptions with newly registered PCa was analyzed. Results In total, 1,528,128 men who took 5ARIs for a mean of 1.523±2.221 years were identified. Among 138,614 patients with PCa, 68,529 (49.4%) took 5ARIs and 70,085 did not. The incidence of PCa was significantly higher in the 5ARI group than in the non-5ARI group during all study years (p<0.001) except for 2007. Adjusted for age, the non-5ARI group had a significantly lower likelihood of PCa detection (hazard ratio [HR], 0.854; p<0.001) and radical prostatectomy, including robot-assisted procedures (HR, 0.834, p<0.001). The mean number of PSA tests was about 2 times higher in the 5ARI group than in the non-5ARI group (3.98 vs. 2.18, p<0.001). Among the subjects who took 5ARIs, the incidence of PCa increased up to 3 years of administration, followed by a decreasing trend thereafter (p<0.001). Conclusions From this observational study in a country with limited PSA testing uptake, the prescription of 5ARIs, for which repeated PSA testing is encouraged to select suitable patients, enhances the detection of PCa, but does not prevent its development.